O Órgão Barroco da Capela da Universidade de Coimbra/The Baroque Organ of Coimbra University Chapel - Joel Canhão (Documentos, 2007)
As a precious piece of artistic heritage embodying the memory of a recent past, the organ of the Coimbra University chapel deserves to be better known. Far from being an exhaustive study, this monograph offers a short reader-friendly account aimed at the general public. From the history of its construction to the selection of the fundamental elements used in its manufacture (including the only keyboard for the command of the three sections), it covers subjects such as its Iberian affiliation, the use of the pedals (suggestions are made for how these might be used), the woodwind and brass, form and positioning of the tubes, etc. It also discusses aesthetic questions connected to hearing and sight, given the excellent quality of the sound of some of the flutes and the luxurious wealth of woodcarving in its frame.